2014
DOI: 10.1155/2014/961375
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Atazanavir: A Retrospective Analysis of Pregnancies Exposed to Atazanavir

Abstract: Introduction. There are few data regarding the tolerability, safety, or efficacy of antenatal atazanavir. We report our clinical experience of atazanavir use in pregnancy. Methods. A retrospective medical records review of atazanavir-exposed pregnancies in 12 London centres between 2004 and 2010. Results. There were 145 pregnancies in 135 women: 89 conceived whilst taking atazanavir-based combination antiretroviral therapy (cART), “preconception” atazanavir exposure; 27 started atazanavir-based cART as “first-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…For each included study, the type of ART and comparisons of timings of ART initiation, along with perinatal outcomes analysed, are displayed in Table 2 2). Only four studies had uniform ART regimens for all timing of ART initiation categories [41,43,45,50]. In all remaining studies, either mixtures of regimens were used across the different ART initiation categories or details were only given for the regimen(s) used in the study as a whole (Appendix 3.1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For each included study, the type of ART and comparisons of timings of ART initiation, along with perinatal outcomes analysed, are displayed in Table 2 2). Only four studies had uniform ART regimens for all timing of ART initiation categories [41,43,45,50]. In all remaining studies, either mixtures of regimens were used across the different ART initiation categories or details were only given for the regimen(s) used in the study as a whole (Appendix 3.1).…”
Section: Resultsmentioning
confidence: 99%
“…The perinatal outcomes reported were preterm birth (18 studies), very preterm birth (six), low birthweight (11), very low birthweight (four), small for gestational age (12), very small for gestational age (three), and neonatal death (two) (Figure 1). The studies, countries, country income status, recruitment periods, number of women analysed, population characteristics, methods to estimate gestational age and correct for confounding, and quality assessments are summarized in Table 1 [6, 16, 18, 30–51].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In one retrospective study involving 155 pregnant women who were exposed to atazanavir, the drug was reported to be generally well tolerated, with 63.2% of the patients reporting no side effects. 4 Nausea was the most commonly observed adverse event (in 34.2% of patients), and about 2% of the women stopped treatment because of side effects. 4 Cholelithiasis was not reported in phase III clinical trials of ritonavir-boosted atazanavir.…”
Section: Introductionmentioning
confidence: 99%
“…4 Nausea was the most commonly observed adverse event (in 34.2% of patients), and about 2% of the women stopped treatment because of side effects. 4 Cholelithiasis was not reported in phase III clinical trials of ritonavir-boosted atazanavir. 3 However, recent postmarketing reports have suggested a potential association between this regimen and cholelithiasis.…”
Section: Introductionmentioning
confidence: 99%